Risiko Klaim Asuransi Jiwa Menggunakan Regresi Cox - Disti Harlin; Minora Longgom Nasution; Yenni Kurniawati (Journal of Mathematics UNP, 2021)
Abstract – Life insurance is one of term for the transfer of risk. The main function of life insurance is as a transfer of risk from the insured to the insurer. Because that function, insurance company are required to determine the factors influencing and know the probability where at a certain time the insured will be many taking insurance claim. The right analysis for this problem is a cox regression model, because this analysis relates to someone survival situasion and the time as main factor. The result of this study indicate that the factors  that affect the risk of insurance claim are factors sex and type of work. Opportunity risk of the insured event occurs by female is    times than the insured event by male. Then the risk of the insured event occurs by outdoor times than the insured event by indoor.Keywords – Life Insurance, Klaim,  Cox Regression.